EDUCAÇÃO E CULTURA NA LUTA POR EMANCIPAÇÃO DA HUMANIDADE: ataques e resistências no governo Bolsonaro - Franklin Douglas Ferreira; Cacilda Rodrigues Cavalcanti; Eblin Cavalcanti; Raquel Dias; Selma Maria Silva de Oliveira Brandão (Revista de Políticas Públicas, 2020)
The role of the media in the education and formation of mass culture in Brazil and the dismantling of public education, higher education and the course of science and technology policy in the Bolsonaro government under the capital project and the rise of the extreme right in Brazil. We analyze the resistance struggles for quality Public Education in Brazil and the attacks of the Bolsonaro government, the School without a Party program and, based on a bibliographic review and documentary research, we evaluate the trends of Brazilian educational policy in Brazil today. For that, it is based on the political thought of the italian Antonio Gramsci, in particular, on his contribution to the understanding of culture and ideology in the struggles for hegemony in society.